Groundwater dynamics and effect of tile drainage on water flow across the redox interface in a Danish Weichsel till area. (January 2019) - Hansen, A.L.; Jakobsen, R.; Refsgaard, J.C.; Højberg, A.L.; Iversen, B.V.; Kjaergaard, C.
Highlights: We investigate groundwater dynamics and the effect of tile drains on flow. We use high-frequency data and a 3D model with detailed representation of drains. Rapid increase in head and drain discharge is seen when autumn water surplus starts. The model was able to capture the dynamics in head and drain discharge. Tile drains significantly decrease the water fluxes across the redox interface. Abstract: Many agricultural soils are tile drained in order to lower water tables and improve crop production, but tile drains have a large impact on water flows and nutrient transport. The objectives of the study were to assess modelling requirements for describing shallow groundwater and tile drainage dynamics and to evaluate how tile drains affect groundwater flow across the redox interface, where nitrate reduction in the subsurface occurs. The study was conducted on a 33-hectare tile drained field within a Weichsel till area in Fensholt catchment, Denmark. The study consisted of 2.5 years high-frequency monitoring and numerical modelling using a variably-saturated 3D hydrological model (FEFLOW) with a detailed representation of the tile drain network. Field data showed extremely rapid increases, up to 1 m per day, in the groundwater heads when the autumn water surplus starts. Drain discharge was found to follow the dynamics in heads. High-frequency monitoring (at least once per day) is therefore necessary in order to capture the dynamics in shallow groundwater and tile discharge. The dynamics showed simultaneous rapid increase in groundwater heads down to a depth of 22 m, illustrating the key importance of deeper geology in understanding the hydrological processes in this area. The temporal dynamics in head and drain discharge were successfully captured by the hydrological model and the steepness of the retention curve was found to be important for this. The calibrated model was successfully tested against discharge in the stream draining a larger area. The model results showed, that tile drains affect the water flow in the area and significantly decrease the downward fluxes across the redox interface, located on average at 3.6 m depth. Tile drains therefore have a large effect on the amount of nitrate reduction in the subsurface and on the nitrate fluxes to receiving surface waters. Graphical abstract: